Cross‐cultural adaptation of the empowerment scale of pregnant women in China context: An integrative method of translation and linguistic validation - Yanjia Liu; Chong Chin Che; Mukhri Hamdan; Mei Chan Chong (Wiley, 2024)
Abstract Aim To translate the Empowerment Scale for Pregnant Women (ESPW) into Chinese and to assess its linguistic validity. Methods The integrative method of the translation process, the Delphi technique, and cognitive interviews were used to implement cross‐cultural adaptation and enhance comprehensibility and linguistic validation. This study recruited 14 experts in the expert review and cognitively reviewed 15 pregnant women. Results The two‐round Delphi method created agreement on cultural applicability. The results of content validity achieved good levels: The item‐level content validity index (CVI) ranged from 0.78 to 1.00, and the scale‐level content validity index, calculated using two different formulas, were 0.97 and 0.81, respectively. Kappa values ranged from 0.74 to 1.00. Pregnant women could understand most of the items and response options in the cognitive interview. The revisions to the wording were made based on suggestions from experts and pregnant women. Conclusion The prefinal simplified Chinese ESPW was semantically and conceptually equivalent to the English version, which was well prepared for further psychometric tests in the next stage of cross‐cultural adaptation. Patient or Public Contribution This comprehensive method successfully developed a Chinese tool to measure the empowerment of pregnant women, indicating the international applicability of this tool and the methodological scientific nature. The simplified Chinese ESPW has the potential to support the identification of empowerment levels of pregnant women and the evaluation of the effectiveness of health education and promotion programmes.